Maternal interleukin-6 and prostaglandin levels post-regiosacral counter-pressure as pain therapy due to uterine contractions - Sri Rejeki; Achmad Solichan; Fitri Nuroini (Media Keperawatan Indonesia, 2021)
Pain is a physiological condition that is generally experienced by almost all mothers in labor or pain during menstruation (dysmenorrhea). Pain causes tachycardia in the mother, increased oxygen consumption, lactic (lactic) acid production, hyperventilation with a risk of respiratory alkalosis, and increased skeletal muscle tension. Regiosarcal Counter Pressure is an effective therapy to reduce pain due to uterine contractions. Based on research that has been done, Regiosarcal counter-pressure therapy can reduce pain levels and has also been shown to slightly reduce prostaglandin (PGE-2) levels in an insignificant amount. Changes in PGE-2 are suspected to have an impact on the stimulant hormone Interleukin-6 (IL-6). This study aims to determine the levels of IL-6 and prostaglandins in the first stage of labor. The research method used quasi-experimental, with inclusion criteria of first-stage labor, no pelvic abnormalities and other abnormalities that hindered the process of vaginal delivery, primiparas, singleton pregnancies, the location of the head did not receive painkillers. The results obtained 25 respondents with an average age of 23.72 (± 2.89) years, the average concentration of IL-6 before therapy was 185.159 (± 3.76) pg/ml and the mean after therapy was 180.782 (± 22.05) pg. /ml, the mean concentration of PGE2 before treatment was 223.521 (± 72.73) pg/ml and the mean after treatment was 179.873 (± 110.61) pg/ml. Administration of regiosacral counter-pressure therapy did not significantly reduce the levels of the hormone IL-6 and prostaglandins in women who experienced uterine contractions.